2022
DOI: 10.1093/ced/llac087
|View full text |Cite
|
Sign up to set email alerts
|

Combination dermoscopy for initiation and monitoring of systemic antifungal therapy for paediatric tinea faciei with invasion of vellus hair owing to Microsporum canis

Abstract: Combination dermoscopy is a simple, noninvasive and accurate technique for the rapid diagnosis, initiation and monitoring of systemic antifungal therapy for tinea faciei caused by Microsporum canis, especially in settings where fungal testing is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Consequently, the recommended treatment strategy for tinea of vellus hair is similar to that of tinea capitis. 8,11,28 Combining the literature review and our report, pathogens were listed in 152 cases (Tables 1, 2, Figure 5). Zoophilic M. canis (61, 40.13%) was the primary causative agent, followed by T. mentagrophytes complex (56, 36.84%), Geophilic Nannizzia gypsea (17,11.18%) was also common, while anthropophilic species such as T. rubrum, T. tonsurans and T. violaceum were less common.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Consequently, the recommended treatment strategy for tinea of vellus hair is similar to that of tinea capitis. 8,11,28 Combining the literature review and our report, pathogens were listed in 152 cases (Tables 1, 2, Figure 5). Zoophilic M. canis (61, 40.13%) was the primary causative agent, followed by T. mentagrophytes complex (56, 36.84%), Geophilic Nannizzia gypsea (17,11.18%) was also common, while anthropophilic species such as T. rubrum, T. tonsurans and T. violaceum were less common.…”
Section: Discussionmentioning
confidence: 87%
“…Gómez‐Moyano and Crespo‐Erchiga 9 suggested that the presence of affected vellus hairs upon direct examination in lesions of tinea of the glabrous skin would be indicative for systemic antifungal therapy. Consequently, the recommended treatment strategy for tinea of vellus hair is similar to that of tinea capitis 8,11,28 …”
Section: Discussionmentioning
confidence: 99%
“…The microorganism is associated with endothrix infection of the hair shaft, including vellus hair. UVFD reportedly shows bright white coiled and curly vellus hair [ 18 , 48 50 ]. These observations may facilitate monitoring therapeutic response and follow-up [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…UVFD reportedly shows bright white coiled and curly vellus hair [ 18 , 48 50 ]. These observations may facilitate monitoring therapeutic response and follow-up [ 50 ]. Normally, non-contact polarized dermatoscopy of Microsporum -induced tinea of the glabrous skin usually shows Morse-code-like hairs (hairs with interrupted black and white bands), bent hairs, zig-zag hairs, and diffuse whitish scaling [ 51 ].…”
Section: Methodsmentioning
confidence: 99%